Facial Expression Processing Is Not Affected by Parkinson’s Disease, but by Age-Related Factors - Derya, Dilara; Kang, June; Kwon, Do-Young; Wallraven, Christian (Frontiers in Psychology, 2019)
The question whether facial expression processing may be impaired in Parkinson’s disease patients so far has yielded equivocal results – existing studies, however, have focused on testing expression processing in recognition tasks with static images of six standard, emotional facial expressions. Given that non-verbal communication also contains non-emotional expression and that input to the brain is usually dynamic, here we address the question of potential facial expression processing differences in a novel format: we test both conversational and emotional, dynamic facial expressions in three groups - Parkinson’s disease patients (n=20), age- and education-matched older healthy controls (n=20), and younger adult healthy controls (n=20). This setup allows us to address both effects of Parkinson’s disease and age-related differences. We employed a multi-dimensional rating task for all groups in which 12 rating dimensions were used to assess evaluative processing of 27 expression videos from 6 different actors. We found that ratings overall were consistent across groups with several rating dimensions (such as arousal or outgoingness) having a strong correlation with the expressions’ motion energy content as measured by optic flow analysis. Most importantly, we found that the Parkinson’s disease group did not differ in any rating dimension from the older healthy control group, indicating highly similar evaluation processing. Both older groups, however, did show significant differences for several rating scales in comparison with the younger adults healthy control group. Looking more closely, older participants rated negative expressions compared to the younger participants as more positive, but also as less natural, persuasive, empathic, and sincere. We interpret these findings in the context of the positivity effect and in-group processing advantages. Overall, our findings do not support processing deficits due to Parkinson’s disease, but rather point to age-related differences in facial expression processing.